Synthesis of a novel series of bispyridinium compounds bearing a xylene linker and evaluation of their reactivation activity against chlorpyrifos-inhibited acetylcholinesterase - Musilek, K; Kuca, K; Jun, D; Dohnal, V; Dolezal, M (Journal of enzyme inhibition and medicinal chemistry, 2005)
Nine potential AChE reactivators were synthesized using a modification of currently known synthetic pathways. Their potency to reactivate AChE inhibited by insecticide chlorpyrifos was tested in vitro. 2,2'-Bis(hydroxyiminomethyl)-1,1'-(1,4-phenylenedimethyl)-bispyridinium dibromide seems to be the most potent AChE reactivator. The reactivation potency of these compounds depends on structural factors such as length of the linking chain between both pyridinium rings and position of the oxime moiety on the pyridinium ring.
Keywords: aktivace enzymů; Animals; Acetylcholinesterase; Enzyme Activation; oximy; Chlorpyrifos; Pyridinium Compounds; Molecular Structure; Structure-Activity Relationship; pyridinové sloučeniny; Cross-Linking Reagents; reagencia zkříženě vázaná; molekulární struktura; Oximes; acetylcholinesterasa; xyleny; Xylenes; krysa rodu Rattus; vztahy mezi strukturou a aktivitou; zvířata; cholinesterasové inhibitory; Cholinesterase Inhibitors; Rats; dursban